Clinical support and perceived competency levels of midwifery students: A descriptive analysis - Hafaza B. Amod; Sipho W. Mkhize (AOSIS, 2022)
Background: Midwifery students in South Africa place great value on the clinical support they receive from midwifery practitioners. Adequate clinical support should help midwifery students to practice procedures safely and independently, allowing them to be competent upon degree completion. Aim: To describe the clinical support and perceived competency levels of midwifery students. Setting: Public hospitals in KwaZulu-Natal. Methods: The researcher chose a quantitative research method using a descriptive design. An all-inclusive purposive and convenience sampling method was undertaken to recruit midwifery students from an undergraduate nursing programme at a university in KwaZulu-Natal. Gatekeepers permission and ethics approval was obtained from the university's registrar and research ethics committee. A self-evaluation questionnaire describing the clinical support and perceived competency levels was completed by 60 respondents. Data were analysed using International Business Machines Corporation Statistical Package for Social Sciences (IBM-SPSS) Version 27. Results: The results highlighted that the clinical support midwifery students received, was beneficial to their clinical learning outcomes. Eighty per cent of clinical support offered to midwifery students was obtained through clinical supervision. Ninety-three per cent of respondents revealed that the clinical support they received were from midwifery practitioners (without a speciality qualification). Although students rated themselves as competent in 88.6% of midwifery procedures, poor outcomes were identified in 11.4% procedures. Conclusion: Midwifery practitioners play a significant role in supporting midwifery students during clinical placement. Advancing the roles of midwifery practitioners through mentorship training is likely to strengthen the quality of clinical support provided and thus improve the competence levels of midwifery students. Contribution: The findings in this paper are valuable in developing clinical support training guidelines for midwifery practitioners.